Територіальна юрисдикція (підсудність) у справах про визначення (зміну) місця проживання дитини та принцип врахування найкращого інтересу дитини - Аніщенко, К. М.; Anishchenko, K. M. (Європейські перспективи. - 2024. - № 3. - С. 70-76, 2024)
У статті розглядаються питання визначення сутності територіальної юрисдикції (підсудності) у справах про визначення (зміну) місця проживання дитини. Правильне визначення місця проживання дитини не тільки істотно впливає на її психофізичний розвиток у дитинстві, а й визначає здебільшого поведінку дорослої людини в майбутньому. Місце проживання дитини може бути визначено з одним із її батьків у разі, якщо батьки з різних причин проживають окремо або мають різне місце проживання. Така ситуація може виникнути, наприклад, у разі розлучення батьків. У цьому випадку питання про визначення місця проживання дитини з одним із батьків може вирішуватися за згодою батьків, у тому числі за спільною згодою батьків і дитини (у разі досягнення дитиною 10 років) і за бажанням дитини (після досягнення нею 14 років). Автор вважає, що при розгляді справ щодо визначення (зміни) місця проживання дитини суди насамперед мають виходити з інтересів самої дитини та балансу між інтересами дитини, правами батьків на виховання дитини й обов’язком батьків діяти в її інтересах.

The article deals with the issue of defi ning the essence of territorial jurisdiction (competence) in cases of determining (changing) the child’s place of residence. The correct defi nition of the child’s place of residence both signifi cantly affects his / her psychophysical development in the childhood and mainly determines the behavior of an adult in the future. The child’s place of residence can be determined with one of the parents if the parents live separately for various reasons, or have different places of residence. Such a situation can arise, for example, in case of parents’ divorce. The issue of determining the child’s place of residence with one of the parents in this case can be settled by the parents consent, including by the joint consent of the parents and the child (if the child is not under 10) and at the request of the child (after the child reaches the age of 14). The author believes that the courts while hearing cases on determining (changing) the child’s place of residence should primarely proceed from the interests of the child and the balance between the interests of the child, the rights of the parents to raise the child, and the duty of the parents to act in the child’s interests. The author considers it possible to agree with N. Volkova that such cases should be руфкв based on the child“s place of residence or location, since it is about protecting the rights and interests of the child, who is the subject of disputed legal relations. It is also necessary to take into account the provisions of the current legislation regarding the expression of the child’s opinion in cases on protecting his / her rights and interests within civil legal proceedings. Therefore, the child in this case must be present in the courtroom to express such an opinion. On the basis of the above, we consider it necessary to legislatively enshrine the provision that claims in cases on protecting the child’s family rights and interests may be heard according to the child’s place of residence at the choice of the plaintiff. The author of the article has proved that the principle of considering the best interests of the child should be a fundamental provision while solving any issues related to the child’s rights and interests.

В статье рассматриваются вопросы определения сущности территориальной юрисдикции (подсудности) по делам об определении (изменении) места жительства ребенка. Правильное определение места жительства ребенка не только оказывает существенное влияние на его психофизическое развитие в детстве, но и определяет в основном поведение взрослого человека в будущем. Место жительства ребенка может быть определен с одним из его родителей в случае, если родители по разным причинам проживают отдельно или имеют разное место жительства. Так ситуация может возникнуть, например, в случае развода родителей. В этом случае вопрос об определении места жительства ребенка с одним из родителей может решаться с согласия родителей, в том числе по общему согласию родителей и ребенка (в случае достижения ребенком 10 лет) и по желанию ребенка (по достижении им 14 лет). Автор считает, что при рассмотрении дел по определении (изменении) места жительства ребенка суды, прежде всего, должны исходить из интересов самого ребенка и баланса между интересами ребенка, правами родителей на воспитание ребенка и обязанностью родителей действовать в его интересах.
Territorial jurisdiction (competence) in cases on determining (changing) the child’s place of residence and the principle of considering the child’s best interests
Keywords: захист сімейних прав та інтересів дитини; територіальна юрисдикція (підсудність); позови у справах про захист сімейних прав та інтересів дитини; дитина; судові спори між батьками щодо визначення місця проживання дитини; найкращі інтереси дитини; protection of the child’s family rights and interests; territorial jurisdiction (competence); claims in cases on protecting the child’s family rights and interests; child; court disputes between parents on determining the child’s place of residence; best interests of a child; защита семейных прав и интересов ребенка; территориальная юрисдикция (подсудность); иски по делам о защите семейных прав и интересов ребенка; ребенок; судебные споры между родителями по определению места жительства ребенка; лучшие интересы ребенка